2021
DOI: 10.1021/acs.macromol.0c02772
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Colloidal Particles Fabricated by Polymerization-Induced Surface Self-Assembly Approach

Abstract: In the past decades, the synthesis of asymmetric colloidal particles has been of wide concern in material science because of their anisotropic morphologies and unique properties. However, the synthesis of the asymmetric particles with controllable anisotropy still remains a big challenge because of the lack of effective methods. In this research, polymerization-induced surface self-assembly (PISSA) approach was demonstrated to be an effective method in the synthesis of colloidal particles with tunable asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…The morphologies of organic-inorganic hybrid nanocomposites can be controlled by changing the molecular weights of the solvophilic block and the solvophobic block. Using a similar strategy, the same group 177 performed PISA mediated by a mixture of a linear macro-CTA dissolved in the reaction medium and CTA-grafted silica nanoparticles. In this case, asymmetric organic-organic hybrid nanoparticles with tunable anisotropy were formed.…”
Section: Polymer Chemistry Reviewmentioning
confidence: 99%
“…The morphologies of organic-inorganic hybrid nanocomposites can be controlled by changing the molecular weights of the solvophilic block and the solvophobic block. Using a similar strategy, the same group 177 performed PISA mediated by a mixture of a linear macro-CTA dissolved in the reaction medium and CTA-grafted silica nanoparticles. In this case, asymmetric organic-organic hybrid nanoparticles with tunable anisotropy were formed.…”
Section: Polymer Chemistry Reviewmentioning
confidence: 99%
“…Recently, Hou and coworkers reported the RAFT dispersion polymerization of styrene using This journal is © The Royal Society of Chemistry 2022 three different chain transfer reagents, 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanyl pentanoic acid (CDTPA), PEG-CTA and SiO 2 -CTA. 218 As shown in Fig. 22, core-shell colloidal particles with SiO 2 in the cores and the polymer assembly in the shells were prepared by PISSA.…”
Section: Surface Nanostructures Fabricated By a Polymerization Induce...mentioning
confidence: 99%
“…In a previous research we found that asymmetric particles with silica cores and polymer layers could be synthesized by a polymerization-induced surface selfassembly (PISSA) approach, and PS homopolymer chains produced in the approach played a key role in the formation of the asymmetric surface structures. 34 Inspired by the research, the effect of the added homopolymer on the surface coassembly of polymer brushes and "free" BCP chains was investigated. Herein, surface coassembly of poly(ethylene glycol)-block-polystyrene (PEG-b-PS) and PS brushes in the presence of PS homopolymer was studied, and we found that the added homopolymer chains were able to induce the fusions of polymer brushes and BCP vesicles, and large compound hybrid structures with multiple cavities on the surfaces were produced.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A variety of surface nanostructures, including spherical and worm-like s-micelles and layered surface structures, are fabricated by the surface coassembly approach. In a previous research we found that asymmetric particles with silica cores and polymer layers could be synthesized by a polymerization-induced surface self-assembly (PISSA) approach, and PS homopolymer chains produced in the approach played a key role in the formation of the asymmetric surface structures . Inspired by the research, the effect of the added homopolymer on the surface coassembly of polymer brushes and “free” BCP chains was investigated.…”
Section: Introductionmentioning
confidence: 99%